Herpes simplex virus encephalitis in a patient receiving ustekinumab associated with extensive cerebral oedema and brainshift successfully treated by immunosuppression with dexamethasone. Issue 8 (13th August 2019) - Van Den Tooren, Harriet Kay; Bharambe, Viraj; Silver, Nicholas; Michael, Benedict D
Abstract : Herpes simplex virus (HSV) encephalitis affects 2–4 people per million/year. Immunocompomised patients can have atypical presentations of HSV encephalitis, including a lack of cerebrospinal fluid (CSF) pleocytosis. We present the case of a patient who was receiving ustekinumab therapy for psoriasis which inhibits interleukin (IL)-12 and IL-23 signalling pathways. The initial presentation was suggestive of encephalitis, but he was discharged prior to the reporting of HSV positivity due to the lack of CSF pleocytosis. On representation, he had worsening symptoms and imaging showed midline shift, indicating cerebral oedema despite the immunosupressant effects of ustekinumab. He required intensive care unit support and treatment with high dose aciclovir and dexamethasone; after a month of treatment he made a good recovery. This case is the first to report a link between ustekinumab and HSV encephalitis, and also emphasises that imunocompromised patients can lack CSF pleocytosis and develop significant cerebral oedema which responds to immune suppression.